Adapted tool for the assessment of domestic violence against women in a low-income country setting: a reliability analysis - Semahegn A; Torpey K; Manu A; Assefa N; Ankomah A (Dove Medical Press, 2019)
Agumasie Semahegn,1,2 Kwasi Torpey,1 Abubakar Manu,1 Nega Assefa,2 Augustine Ankomah1,3 1Department of Population, Family and Reproductive Health, School of Public Health, College of Health Science, University of Ghana, Legon, Accra, Ghana; 2School of Nursing and Midwifery, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 3Population Council, Accra, Ghana Background: One-in-three women has experienced domestic violence, which is a serious public health problem and a human right violation. Domestic violence is a common life experience among women in Ethiopia. The tool used to assess violence against women (VAW) has not been validated to assess its consistency. Cronbach’s alpha (α, or coefficient alpha) is a measure of internal consistency, or reliability, that is, how closely a set of items are related as a group. Reliability is how well a test measures what it should. Therefore, the aim of this study was to estimate the inter-item correlation (reliability) of the tool adapted from literature. Methods: A community-based study was conducted in Northwestern Ethiopia between November 15, 2017 and December 31, 2017. A total of 1,269 women at their permanent place of residence (specifically at their households) were recruited using the multistage stratified systematic sampling method. A structured questionnaire was adapted from literature. Also, 12 trained female data collectors collected the data using the face-to-face interview method. Data were entered into EpiData 3.1.0 and exported to SPSS 23.0 for analysis. Descriptive statistical analysis was carried out to estimate the reliability of the response(s). Results: Overall, Cronbach’s alpha was higher than the minimum recommended value of 0.70. Cronbach’s alpha for specific sections were 0.764 for women’s decision-making autonomy (13 items); women’s accepting attitude toward justified wife-beating (five items, 0.894); physical violence (seven items, 0.876); psychological violence (15 items, 0.925); sexual violence (five items, 0.812); and inequitable gender-norms (seven items, 0.867). Conclusion: The tool used to assess domestic VAW in Northwestern Ethiopia had a high reliability. Therefore, researchers can adapt the tool and further assess its reliability in other settings to have a common and validated tool to study VAW in a low-income countries. Keywords: violence against women, tool reliability analysis, low-income countries